Caution needed in introduction of provisional approvals for medicines. Issue 11 (5th November 2017) - Pace, Jessica; Ghinea, Narcyz; Kerridge, Ian; Lipworth, Wendy
Abstract: The Australian government recently released its response to the Review of Medicines and Medical Devices Regulation, accepting most recommendations. One recommendation involves the introduction of provisional approvals for perceived life‐saving and innovative new treatments, allowing these to be approved on the basis of more limited data on the condition that further safety and efficacy data (including real‐world evidence) are collected to determine whether full approval should be granted. However, experience with similar schemes overseas raises significant questions about the safety and efficacy of products made available through these pathways. These uncertainties are compounded by the challenges associated with the collection and use of 'real‐world' data and the difficulty of withdrawing products from the market once patients and clinicians become familiar with them. Although there may be good reasons to provide patients with earlier access to medicines on the basis of provisional evidence (including providing treatment options and hope to patients with serious illnesses), we must exercise caution in order to protect both current and future patients from potentially harmful and futile treatments and ensure that healthcare systems use their resources wisely.